Intra- and trans-generational costs of reduced female body size caused by food limitation early in life in mites. - Andreas Walzer; Peter Schausberger (PLoS ONE)
Background Food limitation early in life may be compensated for by developmental plasticity resulting in accelerated development enhancing survival at the expense of small adult body size. However and especially for females in non-matching maternal and offspring environments, being smaller than the standard may incur considerable intra- and trans-generational costs. Methodology/principal findings Here, we evaluated the costs of small female body size induced by food limitation early in life in the sexually size-dimorphic predatory mite Phytoseiulus persimilis. Females are larger than males. These predators are adapted to exploit ephemeral spider mite prey patches. The intra- and trans-generational effects of small maternal body size manifested in lower maternal survival probabilities, decreased attractiveness for males, and a reduced number and size of eggs compared to standard-sized females. The trans-generational effects of small maternal body size were sex-specific with small mothers producing small daughters but standard-sized sons. Conclusions/significance Small female body size apparently intensified the well-known costs of sexual activity because mortality of small but not standard-sized females mainly occurred shortly after mating. The disadvantages of small females in mating and egg production may be generally explained by size-associated morphological and physiological constraints. Additionally, size-assortative mate preferences of standard-sized mates may have rendered small females disproportionally unattractive mating partners. We argue that the sex-specific trans-generational effects were due to sexual size dimorphism - females are the larger sex and thus more strongly affected by maternal stress than the smaller males - and to sexually selected lower plasticity of male body size.